Relaksasi untuk Menurunkan Tingkat Stres dan Tekanan Darah pada Penderita Hipertensi - Irfan Fitriadi; Yayi Suryo Prabandari; Indahria Sulistyarini (JIP (Jurnal Intervensi Psikologi), 2011)
This research is aimed to seek for whether relaxation that consists of respiratory relaxation, guide imagery, and hypnosis can decrease stress level and blood pressure on hypertension patients. Subjects in this research are hypertension patients that has blood pressure of 130/80 mmHg or above, lives in in the area of Medical Clinic X of District Sleman, Yogyakarta. Subjects in this research are 28 subjects which are divided into two groups which are 15 subjects in the experiment group and 13 in the control group. Data was obtained by utilizing stress scale. The design of the research is a between group design pretest posttest control group design. Data analysis utilized in this research is t-test. This research indicates that relaxation has been proven to decrease stress level and blood pressure of hypertension patients.Â Keywords: relaxation, stress, blood pressure, and hypertension.